Akebia quinata flower is an excellent potential herbal tea: Chemical quality, bioactivity analysis and metabolite profiles of Akebia quinata flower with different drying methods - Tianjiao Jia; Mian Faisal Nazir; Tao Zhang; Qiuping Zhu; Jie Xu; Longyu Dai; Yafang Zhao; Shuaiyu Zou (Applied Food Research)
Akebia quinata (Houtt.) Decne is a versatile plant with both medicinal and culinary uses. Despite the abundance of A. quinata flowers, they remain underutilised and are often wasted. The effects of different drying methods on the chemical quality, bioactivity and metabolic profiles of A. quinata flowers were compared. Of the three drying methods, microwave drying (MD) had the highest content of phenolics, flavonoids and anthocyanins, the strongest antioxidant capacity. These indices were 1.4–3 times that of those obtained with hot air drying (HD). MD also improved flavor by increasing the concentration of sweet or umami peptides while reducing astringent and bitter compounds. HD and natural drying (ND) retained stronger α-glucoside inhibitory activity and NO inhibitory activity than MD. In general, A. quinata flowers had relatively higher chemical quality and biological activity among the six flower types, highlighting the substantial potential for development as herbal tea. Metabolomic analysis identified 3,902 metabolites, with amino acids, lipids and organic acids being most affected by the drying processes. Considering the quality of the final product, MD was the optimal of the three methods, while ND was suggested to be used in real industrial production due to less energy consumption and economic cost.